Anti-diabetic and anti-inflammatory bioactive hits from Coriaria intermedia Matsum. stem and Dracontomelon dao (Blanco) Merr. & Rolfe bark through bioassay-guided fractionation and liquid chromatography-tandem mass spectrometry - Fabian, Mavis Colleen Porciuncula; Astorga, Rezzaira Marie Neduelan; Atis, Arnelson Arwin Gray; Pilapil, Luis Agustin Elido; Hernandez, Christine Chichioco (Frontiers in Pharmacology, 2024)
Women have been found to be at a higher risk of morbidity and mortality from type 2 diabetes mellitus (T2DM) and asthma. α-Glucosidase inhibitors have been used to treat T2DM, and arachidonic acid 15lipoxygenase (ALOX15) inhibitors have been suggested to be used as treatments for asthma and T2DM. Compounds that inhibit both enzymes may be studied as potential treatments for people with both T2DM and asthma. This study aimed to determine potential anti-diabetic and anti-inflammatory bioactive hits from Coriaria intermedia Matsum. stem and Dracontomelon dao (Blanco) Merr. & Rolfe bark. A bioassay-guided fractionation framework was used to generate bioactive fractions from C. intermedia stem and D. dao bark. Subsequently, dereplication through ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) and database searching was performed to putatively identify the components of one bioactive fraction from each plant. Seven compounds were putatively identified from the C. intermedia stem active fraction, and six of these compounds were putatively identified from this plant for the first time. Nine compounds were putatively identified from the D. dao bark active fraction, and seven of these compounds were putatively identified from this plant for the first time. One putative compound from the C. intermedia stem active fraction (corilagin) has been previously reported to have inhibitory activity against both α-glucosidase and 15lipoxygenase-1. It is suggested that further studies on the potential of corilagin as an anti-diabetic and anti-inflammatory treatment should be pursued based on its several beneficial pharmacological activities and its low reported toxicity.